Dependence of NMR noise line shapes on tuning, matching, and transmission line properties. Issue Volume 44:Issue1(2014) (February 2014) - Bendet‐Taicher, Eli; Müller, Norbert; Jerschow, Alexej
ABSTRACT: The tuning and matching conditions of rf circuits, as well as the properties of the transmission lines connecting these to the preamplifier, have direct consequences for NMR probe sensitivity and as for the optimum delivery of rf power to the sample. In addition, tuning/matching conditions influence radiation damping effects, which manifest themselves as fast signal flip‐back and line broadening effects, and can lead to concentration‐dependent frequency shifts. Previous studies have also shown that the appearance of spin‐noise and absorbed circuit noise signals heavily depended on tuning settings. Consequently, all these phenomena are linked together. The mutual connections and interdependences of these effects are highlighted and reviewed here. © 2014 The Authors Concepts in Magnetic Resonance, Part B: Magnetic Resonance Engineering Published by Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 44B: 1–11, 2014